A coumarin-based reversible two-photon fluorescence probe for imaging glutathione near N-methyl-d-aspartate (NMDA) receptors - Kwon, Nahyun; Lim, Chang Su; Lee, Dayoung; Ko, Gyeongju; Ha, Jeongsun; Cho, Moonyeon; Swamy, K. M.K.; Lee, Eun Young; Lee, Dong Joon; Nam, Sang Jip; Zhou, Xin; Kim, Hwan Myung; et al. (Chemical Communications, 2022)
Glutathione (GSH) is known to play a key role in the modulation of the redox environment in N-methyl-d-aspartate (NMDA) receptors. Coumarin derivative 1 bearing cyanoacrylamide and ifenprodil moieties was synthesized and reported to monitor GSH near NMDA receptors. The cyanoacrylamide moiety allows probe 1 to monitor GSH reversibly at pH 7.4 and the ifenprodil group acts as a directing group for NMDA receptors. Two-photon fluorescence microscopy allows probe 1 to successfully sense endogenous GSH in neuronal cells and hippocampal tissues with excitation at 750 nm. Furthermore, the addition of H2O2 and GSH induced a decrease and an increase in fluorescence emission. Probe 1 can serve as a potential practical imaging tool to get important information on GSH in the brain.
Keywords: Aspartate receptors; Coumarin derivatives; Directing groups; Fluorescence probes; Gluthathione; N-methyl-d-aspartate; Neuronal cell; Synthesised; Two photon fluorescence; Two-photon fluorescence microscopy; Coumarins; Fluorescent Dyes; Glutathione; Hydrogen Peroxide; N-Methylaspartate; Receptors, N-Methyl-D-Aspartate